Media and Cognitive Mobility: Streaming Political Series, Puebla, Mexico 2018 (2020)
This research work analyzes the influence of television series that are broadcast through streaming platforms in Mexico. The research took a representative sample of 400 young people, who were surveyed to know the impact of these communication products in the construction of their perception, political participation and political culture in the last elections of July 2018. Through a quantitative methodology and the use of the statistical sample, belonging to 12 thousand 884 voters from 18 to 19 years old from the capital of Puebla, from the electoral district 12; it was found that there is a low degree of appropriation, the young people surveyed do not determine their perception of Mexican politics from the series they visualize, cognitive mobility is therefore not determinant for this case of the study presented.